Pembelajaran Aritmetika Sosial Berbasis Kisah Islami: Inovasi Modul Kontekstual untuk Penguatan Karakter dan Pemahaman Konsep - Pujilestari, Sri; Sujarwo, Imam; Harini, Sri; Miftakus Surur, Agus; Mohamed, Hasnah Binti (Kaunia: Integration and Interconnection Islam and Science Journal, 2025)
This study aims to describe the integration of Islamic values into the teaching of social arithmetic at the junior high school level through a contextual approach, to identify forms of Islamic value representation within the instructional module, and to explore students’ perceptions of mathematical understanding through an Islamic narrative-based approach. This qualitative descriptive research employed data collection techniques including document analysis of the module, semi-structured interviews, and limited classroom observation. Data were analyzed using Miles and Huberman’s model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that the module “Young Muslim Entrepreneur with Mathematics” successfully integrates Islamic values into social arithmetic content through meaningful storytelling and reflective learning activities. Islamic values are represented through selected Qur’anic verses, hadiths, contextual stories, calculation problems, and learning tasks aligned with sharia principles such as honesty, prohibition of usury (riba), zakat, and social responsibility. Students demonstrated improved conceptual understanding and increased motivation to learn mathematics through this integrative approach. The modules analyzed in this study are the results of the development of the theses of students in the Masters Program in Mathematics Education. These findings suggest that mathematics learning integrated with Islamic values not only enhances cognitive comprehension but also contributes to character formation and students’ spiritual awareness. Penelitian ini bertujuan untuk mendeskripsikan integrasi nilai-nilai Islam dalam pembelajaran aritmetika sosial tingkat SMP melalui pendekatan kontekstual, mengidentifikasi bentuk representasi nilai keislaman dalam modul pembelajaran, serta mengeksplorasi persepsi siswa terhadap pemahaman konsep matematika melalui pendekatan berbasis kisah Islami. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui analisis dokumen modul, wawancara semi-terstruktur, dan observasi terbatas. Analisis data dilakukan dengan model Miles dan Huberman yang mencakup reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa modul “Pengusaha Muslim Muda bersama Matematika” berhasil mengintegrasikan nilai-nilai Islam ke dalam materi aritmetika sosial melalui narasi kontekstual dan aktivitas reflektif. Representasi nilai keislaman ditampilkan dalam bentuk ayat, hadis, konteks kisah, soal perhitungan, dan aktivitas pembelajaran yang mencerminkan prinsip-prinsip syariah seperti kejujuran, larangan riba, zakat, dan tanggung jawab sosial. Siswa menunjukkan pemahaman konsep matematika yang lebih baik serta minat belajar yang meningkat melalui pendekatan ini. Modul yang dianalisis dalam penelitian ini merupakan hasil pengembangan dari tesis mahasiswa Program Magister Pendidikan Matematika. Temuan ini mengindikasikan bahwa pembelajaran matematika berbasis integrasi nilai keislaman tidak hanya memperkuat pemahaman kognitif, tetapi juga berkontribusi pada pembentukan karakter dan kesadaran spiritual peserta didik.